Factors associated with receipt of mammogram among caregivers: a comparison with non-caregivers - Soo Young Kim; Yuqi Guo; Chorong Won; Hee Yun Lee (BMC, 2020)
Abstract Background caregiving responsibilities significantly impact females' decisions on adhering to preventive mammography. The purpose of this study is to examine (1) the levels of mammogram receipt, (2) the role of caregiving factors on the receipt of mammogram in caregiving group, and (3) the role of cancer beliefs on mammogram screening in caregivers and non-caregivers. Methods the 2017 Health Information National Trends Survey (HINTS) provides samples of 1228 women aged 40 to 75 years old for this secondary analysis. By using Andersen's Behavioral Model of Health Services Use, a binomial logistic regression model was used to analyze associations between mammography and socioeconomic factors, caregiving factors, and cancer belief factors. Results caregivers who provided more caregiving hours per week (OR = 0.749, 95% CI = 0.564-0.94) and caregivers who had the belief of rather not knowing the likelihood of getting cancer (OR = 0.673, 95% CI = 0.496-0.914) were less likely to use mammogram. However, caregivers who believed cancer is more common than heart disease (OR = 1.490, 95% CI = 1.302-2.151) were more likely to use a mammogram. Non-caregivers who worried about getting cancer (OR = 1.158, 95% CI = 0.793-1.691) were more likely to use mammogram, but non-caregivers who had the belief of rather not know the likelihood of getting cancer (OR = 0.825, 95% CI = 0.713-0.955) were less likely to use mammogram. Conclusions to support caregivers' breast cancer prevention, caregiving-related policies based on caregiving hours should be developed. Particularly, effort to promote breast cancer screening education and care support among older primary caregivers will likely increase their adherence to preventive mammography uptake. The development of targeted cancer prevention interventions on specific cancer beliefs held by both groups are also urgently needed to promote mammography.